HACCP: An Overview - Jessica A Lepper; Renee M. Goodrich Schneider; Keith R Schneider; Michelle D Danyluk; Aswathy Sreedharan (EDIS)
HACCP is a food safety management system that is used in various segments of the food industry. The objectives of this 4-page fact sheet are to introduce the topic and to summarize the key components of a HACCP program. Written by J. A. Lepper, R. M. Goodrich-Schneider, K. R. Schneider, M. D. Danyluk and A. Sreedharan and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs122